Aging as a Physical Education teacher: a discussion about the body and the profession - doi: 10.4025/reveducfis.v21i4.9123 - Alan Camargo Silva; Sílvia Maria Agatti Lüdorf (Revista da Educação Física)
Aging is an issue that has been studied by different areas. However, there is a gap concerning to studies related to the aging of the teacher of Physical Education. This study aims to discuss some aspects about the aging process, the peculiarities of the profession and the meanings attributed to the body by teachers of Physical Education. Data were collected using deep interviews and open questionnaires with school and university teachers. The aging process was perceived as positive when some attributes were linked positively to the career such as: the acquired knowledge and the search for new ones and the specific understanding about the body. The peculiarity of working in practice, on the other hand, referred to the meaning of the body as a working tool, especially when associated with a youthful stereotype, wearing and to the physical performance.